DIGITAL READING REFLECTION OF ISLAMIC UNIVERSITY STUDENTS: LESSON LEARNED FROM THE PANDEMIC COVID-19 - Umi Rachmawati; Santi Andreyani; Rimajon Sotlikova (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2022)
The teaching of reading during the pandemic Covid-19 is challenging regarding the use of digital reading. The sudden swifts should be conducted by the teachers and the students to deal with the healthy protocols and the instructional goals. This study is aimed at gathering data about the situation at the digital reading class. A qualitative study focusing on the qualitative ethnographic research design was conducted to reveal the current condition of the digital reading class. The results of the study suggest that consideration on the teaching preparation including needs analysis on digital reading, development of the digital reading instruction, and aspects of improving the students’ motivation in digital reading in Islamic university context. The development of the digital reading instruction should respond to the students’ digital reading performance, digital reading motivation, higher order thinking skills, and navigation skills.